Broadband X‐ray ptychography using multi‐wavelength algorithm. (5th January 2021) - Yao, Yudong; Jiang, Yi; Klug, Jeffrey; Nashed, Youssef; Roehrig, Christian; Preissner, Curt; Marin, Fabricio; Wojcik, Michael; Cossairt, Oliver; Cai, Zhonghou; Vogt, Stefan; Lai, Barry; et al.
Abstract : Broadband X‐ray ptychography is developed based on the multi‐wavelength reconstruction method and is systematically demonstrated in both simulation and experiment. In addition, a combined reconstruction approach is proposed to further increase the ptychographic imaging rate. Abstract : Ptychography is a rapidly developing scanning microscopy which is able to view the internal structures of samples at a high resolution beyond the illumination size. The achieved spatial resolution is theoretically dose‐limited. A broadband source can provide much higher flux compared with a monochromatic source; however, it conflicts with the necessary coherence requirements of this coherent diffraction imaging technique. In this paper, a multi‐wavelength reconstruction algorithm has been developed to deal with the broad bandwidth in ptychography. Compared with the latest development of mixed‐state reconstruction approach, this multi‐wavelength approach is more accurate in the physical model, and also considers the spot size variation as a function of energy due to the chromatic focusing optics. Therefore, this method has been proved in both simulation and experiment to significantly improve the reconstruction when the source bandwidth, illumination size and scan step size increase. It is worth mentioning that the accurate and detailed information of the energy spectrum for the incident beam is not required in advance for the proposed method. Further, we combine multi‐wavelength and mixed‐state approaches to jointly solve temporal and spatial partial coherence in ptychography so that it can handle various disadvantageous experimental effects. The significant relaxation in coherence requirements by our approaches allows the use of high‐flux broadband X‐ray sources for high‐efficient and high‐resolution ptychographic imaging.